Macro-economic policy of the European Union in the light of post-Keynesian theory (Economic and Political Thought, 2017)
Within the work on the development of the post-Keynesian theory inthe contemporary economics, attempts made by English classical economistsare continued. The main aim is to explain the issues of economic growth,capital accumulation and technical progress as well as income distribution.The theory explains the reasons for divergent development observed in theNorth and the South of Europe and constitutes grounds for critical assessmentof the European liberalisation and deregulation as well as the adoptedhierarchy of objectives and limits imposed. There are no theoretical reasonsfor the convergence criteria in which there is no employment level, but thereis a priority of inflation, a budget deficit and public debt limit (and a principleof the central bank independence). These have contributed to the aggravationof the effects of the crisis, especially in the countries of Southern Europe.